Rhabdomyosarcoma metastases to the bone marrow of a 2-year-old male patient: A case report - Tri Ratnaningsih; Wirimena Hurimah (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Rhabdomyosarcomas are the most common pediatric soft tissue sarcomas. However, rhabdomyosarcoma cases that manifest as a systemic disease or showing diffuse metastasis in the bone marrow are sporadic. The most common sites of metastasis due to rhabdomyosarcoma include lungs, lymph nodes, and bone marrow. The bone marrow involvement is seen in about 30% of cases of metastasis. We report a case of a 2-year-old boy with complaints of right eye protrusion. The result of a head CT-scan arouses suspicion of rhabdomyosarcoma. On physical examination, protrusion of the eye and swelling of the neck with a fixed and flat surface were observed. Peripheral blood examination resulted in pancytopenia (hemoglobin: 4 g/dL, leukocytes: 3,490 cells/µL, platelets: 16,000 cells/µL). The peripheral blood morphologies showed lymphoblasts and myeloblasts, whereas the bone marrow biopsy result showed infiltration of tumour cells (rosette cell form). Chest imaging examination showed suspected of skeletal metastases in bilateral scapulae and bilateral costae. Pancytopenia with tumour cells metastasis to the bone marrow was found in this case. Diagnosis of rhabdomyosarcoma with multiorgan metastasis and the presence of tumour cells in the bone marrow was based on clinical features, physical examination, laboratory examinations, and other supporting investigations.